1999
DOI: 10.1542/peds.104.1.e10
|View full text |Cite
|
Sign up to set email alerts
|

Kawasaki Disease: More Patients Are Being Diagnosed Who Do Not Meet American Heart Association Criteria

Abstract: Physicians are increasingly likely to diagnose KD in patients who do not meet complete AHA criteria. Despite the potential risks of overdiagnosis and overtreatment, this practice seems justified because the complete criteria are an insensitive indicator of having or developing CAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
99
1
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(112 citation statements)
references
References 9 publications
6
99
1
6
Order By: Relevance
“…This observation has been noted in other studies. [20][21][22] The mean age of the EDG and DDG were not different. The proportion of children Ͻ1 year old in the EDG and DDG was not significantly different (Table 2); however, there were only 19 of 106 children Ͻ1 year old (13 in the EDG and 6 in the DDG).…”
Section: E430mentioning
confidence: 86%
“…This observation has been noted in other studies. [20][21][22] The mean age of the EDG and DDG were not different. The proportion of children Ͻ1 year old in the EDG and DDG was not significantly different (Table 2); however, there were only 19 of 106 children Ͻ1 year old (13 in the EDG and 6 in the DDG).…”
Section: E430mentioning
confidence: 86%
“…Echocardiographic screening for coronary enlargement has shown that a substantial number of children with Kawasaki disease and coronary artery abnormalities are not identified by the classic case definition. [93][94][95] Thus, although the present case definition provides a specific tool for epidemiological surveillance, it may not be the optimal method for aiding clinicians in the recognition of children with a systemic vasculitis that requires prompt treatment. Given the potential seriousness of the complications, together with the efficacy and safety of early treatment, high sensitivity of the treatment criteria is more important than is high specificity.…”
Section: Criteria For Treatment Of Kawasaki Diseasementioning
confidence: 99%
“…Echocardiography has allowed to detect a considerable number of children with KD and CAD who do not meet the standard criteria. 10 Given that the presence of CAD is a very restrictive and specific criterion of incomplete KD, the AHA has developed an algorithm with clinical and analytical criteria for the evaluation and treatment of patients in whom incomplete KD is suspected, which we have used as a gold standard in this study. As in other studies, 11 we have found a longer diagnostic delay in incomplete forms, which, in our case, has been 24 hours (7 versus 6 days) and that in incomplete forms could be related to a higher risk of developing CAD.…”
Section: Discussionmentioning
confidence: 99%